Characteristic Analysis of 10kw Wind Turbine Generator According to Pole/Slot Number Combination - Seo, Sung-Won; Lee, Jeong-In; Jang, Gang-Hyeon; Baek, Chan-Ho; Kim, Kyong-Hwan; Kim, Kyong-Hwan; Hong, Keyyong; Choi, Jang-Young (International Journal of Engineering and Technology, 2018)
Background/Objectives: Modern society has become very dependent on renewable energy, due to both the depletion and environmental problems of fossil energy.Methods/Statistical analysis: Permanent magnet generators vary in performance, depending on their pole/slot combinations. Therefore, in this paper, we compared the characteristics of permanent magnet generators, according to their pole/slot combination. The investigation was conducted using a finite element analysis(FEA) method, and the experiment was validated utilizing an improved version of our previously designed generator and pole/slot combination.Findings: In this paper, two configurations of pole/slot combinations are presented, because of their different characteristics, as highlighted by our analysis. The generator, which was manufactured before the improvements, had an output power of 10kW, with 56 poles and 63 slots. To improve this basic generator, the performance was predicted through finite element analysis (FEA).First, we compared the FEA with the no-load results of the basic model, which verified the reliability of the analysis. Next, the pole/slot combination was changed to 48 poles and 54 slots, with the results analyzed for both no-load and load conditions. To reduce the cogging torque, we adjusted the permanent magnet ratio and applied a chamfering effect, then analyzed the balance of the generators by comparing the radial force density. Finally, an improved model was fabricated and compared with the experimental results to demonstrate its validity.Improvements/Applications: As a result of improving the performance of the generator, this paper can be referenced when manufacturing and improving electric devices.Â